Hubungan Penggunaan Strategi Metakognitif dan Kemampuan Berbahasa Inggris Mahasiswa Pertanian Universitas Kahuripan Kediri - Imam Suhaimi (Muróbbî: Jurnal Ilmu Pendidikan, 2017)
Learning strategies are closely related to student achievement, this study aims to determine objectively one of the language strategies used by students, namely metacognitive strategies, and whether there is a correlation between metacognitive strategies used by students and the students’ English achievement. This research method using quantitative correlation approach. The subjects were students of second semester of Agricultural students of University of Kahuripan Kediri academic year 2016/2017. The results of this study showed that metacognitive strategies, there are 0% of students are categorized as very high, 60% of students are categorized as high, 20% of students are categorized as enough, 13% of students categorized as low, and 7% of students categorized as very low, while students’ English achievement is known as 0% students were categorized as excellent, 60% students are categorized as good, 33% of the students students are categorized as enough, 7% of students categorized as low, and 0% of students categorized as very low. From the analysis using product moment correlation coefficient formula, it can be explained the value of = 0,547 is higher than tabel = 0,514, it can be concluded that H0 was rejected and H1 was accepted. In other words, the use of metacognitive strategies had a positive and significant correlation with English achievement of the second semester students of Agricultural students of University of Kahuripan Kediri academic year 2016/2017.